Noise exposure inside transit buses in Kerman: measurements, drivers and passengers attitudes - Ghorbanali Mohammadi (Iranian Journal of Health, Safety and Environment, 2015)
A comprehensive study was conducted with the objectives of evaluation of noise exposure in the workplace of bus drivers, and to find attitudes of passengers and drivers. This study consisted of two phases. In the first phase, Noise levels were measured in fifty buses. The evaluation of noise levels in the workplace of bus drivers was performed according to the Iranian legislation`s. Twenty four buses with noise levels above 85 dB (A) consider as an "unsafe" workplace. In the second phase, the attitude of 50 male drivers and 500 passengers concerning the annoyance and impact of noise on health were also surveyed. Second phase showed that 70% of drivers and 86.4% of passengers was nervousness from high level noise inside the buses. Eighty four percent drivers and 80% passengers felt noise had affected on their hearing. This study also affirmed that out of every seven drivers, six reported headache.